All-Optical Linear Binary Code Generator Using Optical Nonlinear Material Based Devices - Mandal, Ashis Kumar (International Journal of Computer Sciences and Engineering, 2018)
The transmission of information occurs simultaneously over the same available channel bandwidth in Code Division Multiple Access (CDMA) technique. The spread spectrum (SS) technique is employed in CDMA systems for transmission of information by employing spreading codes. A unique spreading code, acts as a signature code, is assigned for each individual user. The signal occupies a bandwidth much larger than the minimum necessary to send the information in SS modulation technique. A synchronized reception with the code at the receiver is applied for dispreading the information before data recovery. From a long-term, Walsh-Hadamard codes have been employed as spread spectrum codes in CDMA communications due to their ease of generation than the efficiency of these codes. Walsh-Hadamard codes are absolutely orthogonal linear binary codes which have so many favorite applications in synchronous multicarrier communications though they perform poorly for asynchronous multi-user communications. Now, the optical application of these Walsh-Hadamard codes is important for optical CDMA. In these designs nonlinear optical property is exploited for capable of controlling multivalued signals. To this purpose, it is proposed with exploiting the polarization properties of light an all-optical design of Walsh-Hadamard codes generator in this paper.